EFEKTIVITAS INFLUENCER MARKETING UNTUK UMKM DI PANGKALPINANG DAN SUNGAILIAT - Robing Robing; Dian Fitri K (MITZAL (Demokrasi, Komunikasi dan Budaya) : Jurnal Ilmu Pemerintahan dan Ilmu Komunikasi, 2024)
This study is to evaluate the efficacy of influencer marketing as a strategic approach for Micro, Small, and Medium Enterprises (UMKM) in Pangkalpinang and Sungailiat. This research employed a qualitative methodology, conducting semi-structured interviews with 12 UMKM proprietors and various influencers engaged in product marketing collaborations. The results demonstrate that influencer marketing substantially improves the visibility and sales of UMKM products. UMKM proprietors recognized the need of choosing appropriate influencers based on their credibility, audience engagement, and content relevancy to the brand. The study also identified problems, including prices that do not consistently align with outcomes and insufficient control over the content generated by influencers. These findings highlight the significance of influencer marketing within the realm of digital marketing for UMKM in Indonesia. This research aims to offer insights and ideas for UMKM seeking to utilize influencer marketing to improve their market competitiveness.